Students Mathematical Communication Ability through the Brain-Based Learning Approach using Autograph - Triana, Mailis; Zubainur, Cut Morina; Bahrun, Bahrun (Universitas Muhammadiyah Surakarta, 2019)
Studentsâ ability in expressing mathematical ideas in various ways is still not as expected. Teachers need to apply learning method that gives students the opportunity to express mathematical ideas based on their own mindset. Learning with the Brain-Based Learning approach assisted by Autograph software is expected to help students to grow their mathematical communication skills. This study aims to analyze the development of students mathematical communication skills. The subjects of this study were 28 students of class X in one high school in Banda Aceh. The instrument used was a mathematical communication ability test problem. Data analysis techniques was done using descriptive analysis. The results of the study showed that mathematics learning with an Autograph-assisted BBL approach can improve students mathematical communication skills.